2015
DOI: 10.1039/c5ra13265g
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of sandwich polyoxometalates and copper–imidazole complexes for enhancing the peroxidase-like activity

Abstract: Two inorganic–organic hybrids based on copper(ii)–imidazole complex modified sandwich-type tungstobismuthate or tungstoantimonite, have been synthesized, demonstrating higher peroxidase-like activity using TMB as a peroxidase substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Gao et al . synthesized and structurally characterized two new hybrids based on copper(II)-imidazole complex modified sandwich-type tungstobismuthate or tungstoantimonite, Na 4 H 2 [Cu 4 (H 4 im) 12 (H 3 im) 2 ][Cu 3 (H 2 O) 3 (XW 9 O 33 ) 2 ] · nH 2 O (H 4 im = imidazole, H 3 im = deprotonated imidazole, X = Bi, Sb), which demonstrate higher peroxidase-like activity than Keggin-type POMs around physiological pH values in a heterogeneous phase 28 . Sha et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al . synthesized and structurally characterized two new hybrids based on copper(II)-imidazole complex modified sandwich-type tungstobismuthate or tungstoantimonite, Na 4 H 2 [Cu 4 (H 4 im) 12 (H 3 im) 2 ][Cu 3 (H 2 O) 3 (XW 9 O 33 ) 2 ] · nH 2 O (H 4 im = imidazole, H 3 im = deprotonated imidazole, X = Bi, Sb), which demonstrate higher peroxidase-like activity than Keggin-type POMs around physiological pH values in a heterogeneous phase 28 . Sha et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mechanism of catalytic oxidation of TMB may be attributed to hydroxyl radical (•OH) generated from the decomposition of H 2 O 2 [45]. In order to shed light on the catalytic mechanism of the peroxidase-like activity of the NiS/MMT/GO nanocomposites, fluorescent probe as well as ESR technique were used to verify whether •OH generated in the catalytic process.…”
Section: Reaction Mechanism Of Nis/mmt/go Nanocomposites As Peroxidasementioning
confidence: 99%
“…14 They can be applied as both reducing and stabilizing agents in aqueous solutions at room temperature. 15 Furthermore, the ability of the multi-electron redox reaction of POMs make them particularly useful for the synthesis of noble metal nanoparticles. [16][17][18] In recent years, it has become increasingly clear that there is a critical need for green-chemistry-type synthetic routes to new materials.…”
Section: Introductionmentioning
confidence: 99%